Biblioteca Pública Municipal Rosulino Campos: memória, história e leitura - LOPES, Leonardo Montes (2008)
This dissertation offers an analysis of the practices and representations of reading, and also the formation of readers inside the Public Municipal Library Rosulino Campos - PMLRC in the city of Rio Verde Go, and deals with the memory and history of this institution. The work, which is qualitative, was done from bibliography research, and is based in author as Certeau, Halbwachs, Bakhtin, Chartier, Abreu, Melo, Silva, and more. It was done analysis of documents and interviews with six people from the city of Rio Verde who have seen the development of the PMLRC, since its foundation until nowadays. The goal of these interviews was to get information about the memory and history of this place where lies culture and information. Twenty-nine readers of PMLRC were interviewed, and based on these interviews, it was done an analysis about the practice and representation of reading of these people, who came from different social classes, and also were from different ages and literacy. A research to measure the level of support offered by the library to its readers and about projects developed by it to reach these readers also was done. In order to achieve the goal, an analysis about the relationship between the public library and the schools of the city, and the community as well, was approached. The result of the work was amazing. It goes against the most people think about Brazilian s habit of reading. The PMLRC is noted by most of the people who attend it as a valorous public institution which exists to supply the needs of the different readers of the city, supporting them with its materials (books, magazines, newspapers, comic books). The public power is criticized for the lack of investment in the library in different areas: new books, appropriate furniture, conservation of the building and even to hire specialized people. Nevertheless all difficulties, the PMLRC has been a place to build readers and has been done great progress in readers lives, who find in this place an ambient of information, culture and leisure